Manufacturing method of cement mixing pile for soft soil in coastal area

By determining and testing multiple sample parameter groups in cement mixing piles, the parameter group with the best overall performance was selected to manufacture cement mixing piles, thus solving the problem of poor performance of cement mixing piles in the existing technology and achieving performance improvement.

CN120891180AActive Publication Date: 2025-11-04CHINA RAILWAY FIRST GROUP CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511394251.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-28
Publication Date
2025-11-04
Estimated Expiration
2045-09-28

AI Technical Summary

Technical Problem

The existing manufacturing methods for cement mixing piles are relatively simple, resulting in poor performance.

Method used

By determining multiple sample parameter sets, including cement content, phosphogypsum content, and crystal nucleation early strength agent content, multiple cement mixing pile samples were manufactured, and impermeability and compressive strength tests were conducted to obtain permeability coefficient sets and compressive strength coefficient sets. Based on these data, comprehensive parameters were determined, and finally, the sample parameter set with the best comprehensive performance was selected to manufacture cement mixing piles.

Benefits of technology

The overall performance of cement mixing piles has been improved by comprehensively considering permeability and compressive strength parameters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120891180A_ABST
    Figure CN120891180A_ABST
Patent Text Reader

Abstract

The invention provides a manufacturing method of a cement mixing pile for soft soil in a coastal area, and belongs to the field of cement mixing piles, and the method comprises the steps of determining a plurality of sample parameter groups, manufacturing a plurality of cement mixing pile samples corresponding to the plurality of sample parameter groups, and respectively carrying out an anti-permeability test and a compression test on the plurality of cement mixing pile samples. A plurality of cement mixing pile samples are obtained, a permeability coefficient group and a pressure resistance coefficient group of each cement mixing pile sample are obtained, anti-permeability parameters and pressure resistance parameters of each cement mixing pile sample are determined, comprehensive parameters of each cement mixing pile sample in the plurality of cement mixing pile samples are obtained, and the comprehensive parameters are the sum of the pressure resistance parameters and the anti-permeability parameters of the cement mixing pile samples; and the sample parameter set corresponding to the cement mixing pile sample with the maximum comprehensive parameter is determined as the target parameter set, the cement mixing pile is manufactured based on the target parameter set, and the effect of improving the performance of the manufactured cement mixing pile is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of cement mixing pile, and particularly relates to a manufacturing method of cement mixing pile for soft soil in coastal areas. BACKGROUND

[0002] The cement mixing pile is an underground structure for reinforcing soft soil foundation.

[0003] In a manufacturing method of a cement mixing pile, a plurality of cement mixing pile samples are manufactured based on different parameters, and after the manufacturing, strength tests are performed on each sample to determine the sample with the highest strength, and then the cement mixing pile can be manufactured according to the parameters corresponding to the sample with the highest strength.

[0004] However, in the above method, the process of determining the parameters for manufacturing the cement mixing pile is relatively single, which leads to poor performance of the manufactured cement mixing pile. SUMMARY

[0005] Embodiments of the present application provide a manufacturing method of cement mixing pile for soft soil in coastal areas, which can solve the problem of poor performance of cement mixing pile in the related art. The technical solution is as follows: According to a first aspect of the present application, a manufacturing method of cement mixing pile for soft soil in coastal areas is provided, which is used for manufacturing the cement mixing pile applied to the soft soil foundation in the coastal area, and the method comprises the following steps: determining a plurality of sample parameter groups, each of the sample parameter groups comprising a cement mixing amount, a phosphogypsum mixing amount and a crystal nucleus early strength agent mixing amount in the cement mixing pile, and at least one of the cement mixing amount, the phosphogypsum mixing amount and the crystal nucleus early strength agent mixing amount in any two of the sample parameter groups is different; manufacturing a plurality of cement mixing pile samples corresponding to the plurality of sample parameter groups; performing impermeability tests and compression tests on the plurality of cement mixing pile samples respectively, and obtaining a permeability coefficient group and a compression coefficient group of each of the cement mixing pile samples, the permeability coefficient group comprising a permeability coefficient of the cement mixing pile sample on the n th day after manufacturing and a permeability coefficient on the 4n th day, the compression coefficient group comprising an unconfined compressive strength of the cement mixing pile sample on the n th day after manufacturing and an unconfined compressive strength on the 4n th day, and n≥7; determining an impermeability parameter of each of the cement mixing pile samples based on the permeability coefficient group of the plurality of cement mixing pile samples, the impermeability parameter being negatively correlated with the permeability coefficient in the permeability coefficient group; determining a compression parameter of each of the cement mixing pile samples based on the compression coefficient group of the plurality of cement mixing pile samples, the compression parameter being positively correlated with the unconfined compressive strength in the compression coefficient group; obtaining a comprehensive parameter of each cement mixing pile sample in the plurality of cement mixing pile samples, the comprehensive parameter being a sum of a compression parameter and an impermeability parameter of the cement mixing pile sample; determining a sample parameter group corresponding to the cement mixing pile sample with the largest comprehensive parameter as a target parameter group; manufacturing the cement mixing pile based on the target parameter group.

[0006] Optionally, each of the cement mixing pile samples includes at least one impermeability sample and at least one compression sample; The impermeability test and the compression test on the plurality of cement mixing pile samples respectively include: performing an impermeability test on the impermeability sample, and obtaining a permeability coefficient of the impermeability sample on the nth day after manufacturing and a permeability coefficient on the 4nth day based on a permeability coefficient calculation formula, the permeability coefficient calculation formula including: ; wherein k t is the permeability coefficient, Q is the total amount of seepage in time t, L is the distance of the pressure measuring hole when the impermeability test is performed on the impermeability sample, A is the cross-sectional area of the impermeability sample, H is the water head difference, and T is time; performing a compression test on the compression sample.

[0007] Optionally, the determination of the impermeability parameter of each cement mixing pile sample based on the permeability coefficients of the plurality of cement mixing pile samples includes: sorting the impermeability samples in the plurality of cement mixing pile samples based on permeability parameter sums of the plurality of cement mixing pile samples to obtain an impermeability sample sequence, the permeability parameter sum being a sum of the permeability coefficient of the impermeability sample on the nth day after manufacturing and the permeability coefficient on the 4nth day, and the sequence number of each impermeability sample in the impermeability sample sequence being negatively correlated with the permeability parameter sum of the cement mixing pile sample in which the impermeability sample is located; determining the sequence number of each impermeability sample as the impermeability parameter of the cement mixing pile sample in which the impermeability sample is located.

[0008] Optionally, the determination of the compression parameter of each cement mixing pile sample based on the compression coefficients of the plurality of cement mixing pile samples includes: sorting the compression samples in the plurality of cement mixing pile samples based on compression parameter sums of the plurality of cement mixing pile samples to obtain a compression sample sequence, the compression parameter sum being a sum of the unconfined compressive strength of the compression sample on the nth day after manufacturing and the unconfined compressive strength on the 4nth day, and the sequence number of each compression sample in the compression sample sequence being positively correlated with the compression parameter sum of the cement mixing pile sample in which the compression sample is located. determining a serial number of each of the compression-resistant samples as a compression parameter of a cement mixing pile sample in which each of the compression-resistant samples is located.

[0009] Optionally, the determining the plurality of sample parameter groups comprises: determining three cement contents, the three cement contents being 15%, 20% and 25% respectively, the cement content being a mass ratio of cement to clay in the cement mixing pile; determining three phosphogypsum contents, the three phosphogypsum contents being 10%, 20% and 30% respectively, the phosphogypsum content being a mass ratio of phosphogypsum to clay in the cement mixing pile; determining three crystal nucleus early strength agent contents, the three crystal nucleus early strength agent contents being 0.5%, 1% and 1.5% respectively, the crystal nucleus early strength agent content being a mass ratio of crystal nucleus early strength agent to clay in the cement mixing pile; obtaining nine sample parameter groups based on the three cement contents, the three phosphogypsum contents and the three crystal nucleus early strength agent contents and the orthogonal test method.

[0010] Optionally, the manufacturing the plurality of cement mixing pile samples corresponding to the plurality of sample parameter groups comprises: obtaining clay in the soft soil subgrade; drying the clay and screening impurities in the clay through a sieve to obtain screened clay; adding water to the screened clay to obtain target clay, a water content in the target clay being same as a water content in the clay in the soft soil subgrade; obtaining cement, phosphogypsum and crystal nucleus early strength agent based on a cement content, a phosphogypsum content and a crystal nucleus early strength agent content in a first sample parameter group in the plurality of sample parameter groups; dissolving the crystal nucleus early strength agent into water, and stirring and mixing the cement and the phosphogypsum according to a water-solid ratio of 0.5 to obtain cement slurry; loading the cement slurry into a mold of the cement mixing pile sample; placing the mold loaded with the cement slurry into a standard curing chamber for 24 hours; demolding the mold to obtain the cement mixing pile sample.

[0011] Optionally, the mass ratio of the components in the cement comprises 27.19% of silicon dioxide, 11.32% of aluminum trioxide, 3.76% of iron trioxide, 51.78% of calcium oxide, 1.98% of magnesium oxide and 3.97% of sulfur trioxide. Optionally, the mass ratio of the components in the phosphogypsum comprises 9.01% of silicon dioxide, 2.01% of aluminum oxide, 0.49% of iron trioxide, 35.41% of calcium oxide, 0.21% of magnesium oxide, and 52.87% of sulfur trioxide.

[0012] Optionally, the method further comprises: Optionally, the method further comprises:

[0013] Optionally, before determining the compressive parameter of each cement mixing pile sample based on the compressive parameter groups of the plurality of cement mixing pile samples, the method further comprises: Optionally, before determining the compressive parameter of each cement mixing pile sample based on the compressive parameter groups of the plurality of cement mixing pile samples, the method further comprises: Optionally, before determining the compressive parameter of each cement mixing pile sample based on the compressive parameter groups of the plurality of cement mixing pile samples, the method further comprises:

[0014] The technical scheme provided by the embodiments has at least the following beneficial effects: By respectively performing the impermeability test and the compressive test on the plurality of cement mixing pile samples, the permeability parameter group and the compressive parameter group of each cement mixing pile sample are obtained, and the permeability parameter group and the compressive parameter group both include the data of the nth day and the 4nth day, then the impermeability parameter and the compressive parameter of each cement mixing pile sample are determined based on the data, and further the comprehensive parameter of each cement mixing pile sample is obtained, then the cement mixing pile sample corresponding to the sample parameter group with the maximum comprehensive parameter can be used to manufacture the cement mixing pile. The method not only comprehensively considers the permeability parameter and the compressive parameter of the cement mixing pile sample, but also respectively obtains these parameters at different times, and comprehensively considers the overall performance of the cement mixing pile sample manufactured by different sample parameter groups, thereby achieving the effect of improving the performance of the manufactured cement mixing pile. BRIEF DESCRIPTION OF DRAWINGS

[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings needed in the embodiment description will be briefly introduced. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without creative labor.

[0016] Figure 1 This is a flowchart illustrating a method for manufacturing cement mixing piles in soft soil in coastal areas, as provided in an embodiment of this application. Figure 2 This is a flowchart of another method for manufacturing cement mixing piles in soft soil in coastal areas, provided in an embodiment of this application.

[0017] The accompanying drawings illustrate specific embodiments of this application, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the concept in any way, but rather to illustrate the concept of this application to those skilled in the art through reference to particular embodiments. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of this application clearer, the embodiments of this application will be described in further detail below with reference to the accompanying drawings.

[0019] Figure 1 This is a flowchart illustrating a method for manufacturing cement-mixed piles in soft soil in coastal areas, as provided in an embodiment of this application. The method is used to manufacture cement-mixed piles for use in soft soil roadbeds in coastal areas. The method includes: Step 101: Determine multiple sample parameter groups. Each sample parameter group includes the cement content, phosphogypsum content, and crystal nucleation early strength agent content in the cement mixing pile. At least one of the cement content, phosphogypsum content, and crystal nucleation early strength agent content in any two sample parameter groups is different.

[0020] Step 102: Create multiple cement mixing pile samples corresponding to multiple sample parameter groups.

[0021] Step 103: Perform permeability and compressive strength tests on multiple cement mixing pile samples respectively, and obtain the permeability coefficient group and compressive strength coefficient group for each cement mixing pile sample. The permeability coefficient group includes the permeability coefficient of the cement mixing pile sample on the nth day after manufacturing and the permeability coefficient on the 4nth day after manufacturing. The compressive strength coefficient group includes the unconfined compressive strength of the cement mixing pile sample on the nth day after manufacturing and the unconfined compressive strength on the 4nth day after manufacturing, where n≥7.

[0022] Step 104: Based on the permeability coefficient group of multiple cement mixing pile samples, determine the anti-seepage parameter of each cement mixing pile sample. The anti-seepage parameter is negatively correlated with the permeability coefficient in the permeability coefficient group.

[0023] Step 105: Based on the compressive coefficient group of multiple cement mixing pile samples, determine the compressive parameters of each cement mixing pile sample. The compressive parameters are positively correlated with the unconfined compressive strength in the compressive coefficient group.

[0024] Step 106: Obtain the comprehensive parameters of each cement mixing pile sample from multiple cement mixing pile samples. The comprehensive parameters are the sum of the compressive strength parameters and the impermeability parameters of the cement mixing pile sample.

[0025] Step 107: Determine the sample parameter group corresponding to the cement mixing pile sample with the largest comprehensive parameters as the target parameter group.

[0026] Step 108: Manufacture cement mixing piles based on the target parameter set.

[0027] In summary, the method for manufacturing cement-mixed piles in soft soil in coastal areas provided in this application involves conducting permeability and compressive strength tests on multiple cement-mixed pile samples to obtain permeability and compressive strength coefficient sets for each sample. Both sets include data from day n and day 4n. Based on these data, the permeability and compressive strength parameters for each sample are determined, and a comprehensive parameter for each sample is obtained. Cement-mixed piles can then be manufactured based on the parameter set corresponding to the sample with the highest comprehensive parameter. This method not only comprehensively considers the permeability and compressive strength parameters of the cement-mixed pile samples but also acquires these parameters at different times and considers the overall performance of cement-mixed pile samples manufactured from different parameter sets, thereby improving the performance of the manufactured cement-mixed piles.

[0028] Figure 2 This is a flowchart illustrating another method for manufacturing cement-mixed piles in soft soil in coastal areas, provided in an embodiment of this application. This method is used to manufacture cement-mixed piles for use in soft soil roadbeds in coastal areas. The method includes: Step 201: Determine multiple sample parameter groups.

[0029] The method provided in this application is a method involving foundation treatment and reinforcement, excavation, and filling.

[0030] Each sample parameter group includes the cement content, phosphogypsum content, and nucleation agent content in the cement-mixed pile, and at least one of these three contents must be different between any two sample parameter groups. Three cement contents are determined: A1, A2, and A3 are 15%, 20%, and 25%, respectively. The cement content is the mass ratio of cement to clay in the cement-mixed pile. Three phosphogypsum dosages were determined: B1, B2, and B3, which were 10%, 20%, and 30%, respectively. The phosphogypsum dosage was the mass ratio of phosphogypsum to clay in the cement mixing pile. The dosages of the three early-strength nucleation agents were determined. The dosages of the three early-strength nucleation agents C1, C2, and C3 were 0.5%, 1%, and 1.5%, respectively. The dosage of the early-strength nucleation agent was the mass ratio of the early-strength nucleation agent to the clay in the cement mixing pile. Nine sample parameter groups were obtained based on three cement admixtures, three phosphogypsum admixtures, and three nucleation early strength agent admixtures, using orthogonal experimental methods. See Table 1 for details. Table 1 Orthogonal array for experiments

[0031] Step 202: Create multiple cement mixing pile samples corresponding to multiple sample parameter groups.

[0032] Step 202 includes: 1. Obtain clay from the soft soil subgrade.

[0033] 2. The clay is dried and impurities are removed by sieving. The drying process can be air-drying or other methods, which are not limited in this embodiment. After the clay is completely dry, impurities are removed by sieving with a 2mm mesh size. The mesh size can also be 1mm, 3mm, or other values, which are not limited in this embodiment.

[0034] 3. Add water to the sieved clay to obtain the target clay. The moisture content of the target clay is the same as that of the clay in the soft soil subgrade.

[0035] The unit weight of the target clay particles is 19.1 kN / m³. 3 Permeability coefficient 9.1×10 -3 The soil density is 19.4%, with a density of 100 cm / s, a water content of 22.8%, a liquid limit of 28.6%, a plastic limit of 19.4%, and a plasticity index of 9.2. The unit weight of soil particles refers to the weight of soil particles per unit volume. The water content is the percentage of the mass of water in the soil relative to the mass of solid particles. The permeability coefficient characterizes the ability of soil to be permeated by water. The liquid limit is the critical water content at which soil transitions from a plastic to a fluid state. The plastic limit is the critical water content at which soil transitions from a plastic to a semi-solid state. The plasticity index indicates the range of water content within the plastic state.

[0036] 4. Based on the cement content, phosphogypsum content, and crystal nucleation early strength agent content in the first sample parameter group among multiple sample parameter groups, obtain the cement, phosphogypsum, and crystal nucleation early strength agent.

[0037] The cement is ordinary Portland cement with a strength grade of 42.5 MPa. The mass proportions of the cement components include: 27.19% silicon dioxide, 11.32% aluminum oxide, 3.76% ferric oxide, 51.78% calcium oxide, 1.98% magnesium oxide, and 3.97% sulfur trioxide. Phosphogypsum is a byproduct left after sulfuric acid treatment of phosphate rock to extract phosphoric acid. The mass proportions of the components in phosphogypsum include: 9.01% silicon dioxide, 2.01% aluminum oxide, 0.49% ferric oxide, 35.41% calcium oxide, 0.21% magnesium oxide, and 52.87% sulfur trioxide.

[0038] The nucleation accelerator is a white powder with an effective content of 50% (the "nucleus" substance accounts for 50% of the total mass of the nucleation accelerator powder) and a density of 1.15 g / cm3. Its function is to promote cement hydration and improve the early strength of concrete.

[0039] 5. Dissolve the nucleation early strength agent in water, and mix the cement and phosphogypsum at a water-to-solid ratio of 0.5 to obtain cement slurry.

[0040] 6. Pour the cement slurry into the mold of the cement mixing pile sample.

[0041] Cement slurry is injected into an anti-permeability mold and a pressure-resistant mold. Both the anti-permeability mold and the pressure-resistant mold are columnar. The anti-permeability mold has a diameter of 39.1 mm and a height of 80 mm, and the pressure-resistant mold has a diameter of 50 mm and a height of 100 mm. The anti-permeability mold is used to manufacture anti-permeability samples, and the pressure-resistant mold is used to manufacture pressure-resistant samples. The anti-permeability mold and the pressure-resistant mold can also be other shapes, which are not limited in the embodiments of this application.

[0042] 7. Place the mold containing cement slurry into the curing room and let it stand for 24 hours.

[0043] 8. Demold the mold to obtain a cement mixing pile sample.

[0044] Step 203: Perform impermeability tests and compressive strength tests on multiple cement mixing pile samples respectively, and obtain the permeability coefficient group and compressive strength coefficient group for each cement mixing pile sample.

[0045] The permeability coefficient group includes the permeability coefficient of the cement mixing pile sample on the nth day after manufacturing and the permeability coefficient on the 4nth day after manufacturing; the compressive strength coefficient group includes the unconfined compressive strength of the cement mixing pile sample on the nth day after manufacturing and the unconfined compressive strength on the 4nth day after manufacturing, n≥7; each cement mixing pile sample includes at least one impermeable sample and at least one compressive strength sample.

[0046] Step 203 includes: 1. Conduct permeability tests on the anti-permeability samples, and obtain the permeability coefficient of the anti-permeability samples on the nth day after manufacturing and on the 4nth day based on the permeability coefficient calculation formula. The permeability coefficient calculation formula includes: ; Where, k t Where is the permeability coefficient, Q is the total seepage in time t, L is the spacing of the pressure testing holes when testing the anti-seepage sample, A is the cross-sectional area of ​​the anti-seepage sample, H is the hydraulic head difference, and T is time. In one embodiment provided in this application, when n is 7 and 4n is 28, based on the 9 sample parameter groups obtained in Table 1, the permeability coefficient of the anti-permeability sample on the 7th day and the permeability coefficient on the 28th day after manufacturing are obtained through the above permeability coefficient calculation formula, as shown in Table 2 below: Table 2

[0047] The table above shows that the permeability coefficient of group A2B2C3 was the lowest on day 7, at 2.05 × 10⁻⁶. -7 On day 28, the permeability coefficient of group A3B1C2 was the lowest at 1.89 × 10 cm / s. -7 cm / s. Furthermore, a comparison revealed that when the gypsum content was 30% of the cement mass, the permeability coefficient of the cement-soil significantly increased. This indicates that excessive gypsum content increased the amount of ettringite in the cement-soil paste, and its volume expansion increased the porosity of the paste, thus improving the permeability coefficient of the cement-soil. Therefore, the permeability coefficients of the anti-seepage samples on day 7 and day 28 were further analyzed using range and variance. Table 3 shows the range analysis of the permeability coefficients of the anti-seepage samples: Table 3

[0048] In Table 3 above, R represents the range, and k represents the average of all test results for a certain factor (e.g., cement content A) at level n. For example, k1 represents the average of all test results for cement content A at level 1. The table shows that the three factors resulted in different changes in the permeability coefficient of the anti-permeability samples on days 7 and 28. For day 7, the influencing factors on the permeability coefficient were B > A > C, i.e., phosphogypsum content > cement content > accelerator content. The change in phosphogypsum content had the most significant impact on permeability on day 7. Similarly, on day 28, the influencing factors on the permeability coefficient were B > A > C, i.e., phosphogypsum content > cement content > accelerator content, which is consistent with the results on day 7. When the amount of gypsum used is low, the amount of ettringite generated is low, mainly playing a filling role in the cement-soil, increasing its density, reducing the overall porosity, and thus decreasing the permeability coefficient of the cement-soil. Early-strength agents primarily promote cement hydration, increase overall density, and reduce the permeability of cement-soil mixtures. However, their effect weakens around day 28, similar to the changes in strength. On day 28, the amount of gypsum added has the greatest impact on the permeability of cement-soil mixtures. A small amount densifies the overall structure, while an excessive amount generates ettringite, which expands in volume, disrupting the slurry and increasing overall micro-cracks, thus increasing the permeability of the cement-soil mixture. Therefore, its impact is greater than that of cement and early-strength agents.

[0049] In this embodiment of the application, an analysis of variance was also performed on the permeability coefficient of the anti-permeability sample. By performing statistical analysis on the permeability coefficient of the sample, the significance of the influence between each variable and the response value was studied. The analysis of variance of the permeability coefficient is shown in Table 4 below: Table 4

[0050] In Table 4 above, "-" in the significance indicator indicates no significance. "" indicates general significance, SS is the sum of squares, df is the degrees of freedom, F-value is the ratio of the mean square between groups to the mean square within groups, and P-value is the direct reflection of the significance level. From the variance results in Table 4, it can be seen that on days 7 and 28, the cement dosage and the early-strength agent dosage had no significant effect on the permeability coefficient of the samples, while the effect of phosphogypsum was significant. The main reason is that excessive phosphogypsum may cause micro-expansion of the slurry, which weakens the density and strength, thus increasing the permeability coefficient. A small amount has a promoting effect, reducing the permeability coefficient of the samples, exhibiting two opposite effects. Therefore, the effect of ettringite on the permeability coefficient of cement-soil is more significant.

[0051] 2. Conduct a compression resistance test on the compression-resistant sample.

[0052] Permeability and compressive strength tests can be conducted according to the methods and procedures specified in the Chinese transportation industry standard "Specifications for Geotechnical Testing of Highways" (JTG 3430-2020).

[0053] In one embodiment provided in this application, when n is 7 and 4n is 28, the 9 sample parameter groups obtained in Table 1 are used as compression samples for compression testing. The unconfined compressive strength of the 9 compressive strength coefficient groups on the 7th day after manufacturing and the unconfined compressive strength on the 28th day are obtained, as shown in Table 5 below: Table 5

[0054] As can be seen from Table 5 above, the cement-soil of group A3B2C1 had the highest compressive strength on day 7, at 2.25 MPa. However, by day 28, the group with the highest compressive strength was group A3B1C2 at 3.95 MPa, which was 0.46 MPa higher than that of group A3B2C1.

[0055] Range analysis was performed on the unconfined compressive strength of the above-mentioned compressive samples on day 7 and day 28, as shown in Table 6 below: Table 6

[0056] In Table 6 above, R represents the range, and k represents the average of all test results for a certain factor (e.g., cement content A) at the nth level. The three factors showed different changes in the strength of the compressive strength samples on day 7 and day 28. For day 7 strength, the influencing factors were in the order A>C>B, i.e., cement content > accelerator content > phosphogypsum content, with the cement content change having the most significant effect on day 7 strength. The optimal mix ratio at this point was A3B2C3, i.e., cement:phosphogypsum:accelerator = 25%:20%:1.5%. The reason for this change is that a higher cement content increases the amount participating in the hydration reaction, resulting in more hydration products, promoting the density of the cement-soil, and improving its unconfined compressive strength. Meanwhile, with a small amount of gypsum, ettringite is formed during the cement hydration reaction. However, as the phosphogypsum content increases, the excessive increase in ettringite can lead to an overall increase in volume, potentially compromising the density of the cementitious structure. The addition of an accelerator provides more nucleation sites, promotes cement hydration, forms more CSH gel, and a denser paste, while also inhibiting the damage caused by excessive ettringite to some extent. On day 28, the influence of various factors on the strength of the compressive strength samples differed slightly from that on day 7. The order of influencing factors was A>B>C, i.e., cement content>phosphogypsum content>accelerator content. Changes in cement content still had the most significant impact on strength on day 28, while changes in accelerator content had the weakest effect. The optimal mix ratio at this point was A3B1C2, i.e., cement:phosphogypsum:accelerator = 25%:10%:1%. By day 28, cement remained the primary source of strength, and the effect of the accelerator gradually weakened. A suitable phosphogypsum content was 10%, ensuring sufficient ettringite content without excessive ettringite affecting strength changes.

[0057] In this embodiment of the application, an analysis of variance was also performed on the strength of the compression sample. By performing statistical analysis on the strength of the sample, the significance of the influence between each variable and the response value was studied. The analysis of variance of the strength is shown in Table 7 below: Table 7

[0058] In Table 7 above, "-" in the significance indicator indicates no significance. "Indicates general significance" "" indicates highly significant, SS is the sum of squares, df is the degrees of freedom, F is the ratio of the mean square between groups to the mean square within groups, and P is the value reflecting the significance level. From the variance results in Table 7, it can be seen that on day 7, cement has a significant impact on the strength of the compressive strength samples, while the effects of the accelerator and phosphogypsum are not significant. However, on day 28, all three factors have significant effects on strength, with cement contributing the most to the strength of the compressive strength samples, followed by gypsum, and the accelerator being the weakest. The main reason is that the accelerator can exert its nucleation effect before day 7, enabling the cement to hydrate rapidly and improving the early strength of the compressive strength samples. However, on day 28, the effect of the accelerator is weakened, and the excessive ettringite produced by phosphogypsum may cause micro-expansion of the paste, which weakens the strength, resulting in a negative impact and a significant change in the results.

[0059] Step 204: Determine whether there is a compressive coefficient group among the multiple cement mixing pile samples whose unconfined compressive strength on the 4nth day after manufacturing is less than the preset unconfined compressive strength; if so, proceed to step 205; if not, proceed to step 206.

[0060] In one embodiment provided in this application, the preset unconfined compressive strength is greater than or equal to 3.5 MPa. It is confirmed that the unconfined compressive strength of the nine compressive strength coefficient groups in Table 5 above is less than 3.5 MPa on the 28th day. The preset unconfined compressive strength can also be other values, and this embodiment of the application does not limit it.

[0061] Step 205: Remove the compressive strength coefficient group whose unconfined compressive strength on the 4nth day after manufacturing is less than the preset unconfined compressive strength. Proceed to step 206.

[0062] In one embodiment provided in this application, as shown in Table 5, among the nine compressive strength groups, only compressive strength group A3B1C2 has an unconfined compressive strength of 3.95 MPa on day 28, which is greater than or equal to 3.5 MPa. That is, the unconfined compressive strength of all other compressive strength groups except A3B1C2 is less than the preset unconfined compressive strength on day 4n after manufacturing. Therefore, the other compressive strength groups except A3B1C2 can be removed. Of course, the above is merely an example of this application; the preset unconfined compressive strength can be any value, and this embodiment does not limit the specific value.

[0063] Step 206: Based on the permeability parameters of multiple cement mixing pile samples, sort the anti-permeability samples among the multiple cement mixing pile samples to obtain the anti-permeability sample sequence.

[0064] The permeability parameter is the sum of the permeability coefficients of the anti-permeability samples in the cement mixing pile sample on the nth day after manufacturing and the permeability coefficient on the 4nth day. In the anti-permeability sample sequence, the number of each anti-permeability sample is negatively correlated with the permeability parameter of the cement mixing pile sample in which it belongs. For example, as shown in Table 2 above, the permeability parameters of impermeable samples A1B1C3 are the same as the permeability coefficient of the impermeable sample in the cement mixing pile samples on the 7th day after manufacturing, which is 12.98 × 10⁻⁶. -7 cm / s plus the permeability coefficient of 2.89 × 10 on day 28 -7 cm / s, which is 15.87 × 10 -7 cm / s. After calculating the permeability parameters of all the anti-seepage samples, the nine anti-seepage samples in Table 2 above were sorted according to the negative correlation between the serial number of each anti-seepage sample and the permeability parameters of the cement mixing pile sample to which it belongs, resulting in the following serial numbers 1 to 9: Sample A2B3C2 (No. 1) has a total permeability parameter of 67.8 × 10⁻⁶. -7 cm / s; for impermeable sample A3B3C3, the sum of the permeability parameters is 52 × 10 cm / s; -7 cm / s; the total permeability parameter of sample A1B3C1 (sample number 3) is 48.6 × 10⁻⁶ cm / s. -7 cm / s; Sample No. 4, A3B2C1, has a total permeability parameter of 21.54 × 10 cm / s. -7 cm / s; for sample A2B2C3 (sample number 5), the sum of the permeability parameters is 19.02 × 10 cm / s. - 7 cm / s; for impermeable sample A1B1C3 (sample number 6), the sum of the permeability parameters is 15.87 × 10 cm / s. -7 cm / s; for impermeable sample A1B2C2 (sample number 7), the sum of the permeability parameters is 15.09 × 10⁻⁶ cm / s. -7 cm / s; the total permeability parameter of sample A2B1C1 (sample number 8) is 13.95 × 10⁻⁶ cm / s. -7 cm / s; for sample A3B1C2 (sample number 9), the total permeability parameter is 8.07 × 10⁻⁶ cm / s. -7 cm / s.

[0065] Step 207: Determine the permeability parameter of the cement mixing pile sample to which each permeability sample belongs by its serial number.

[0066] In this step, the serial number of any anti-seepage sample can be used to determine the anti-seepage parameter of the cement mixing pile sample to which each anti-seepage sample belongs. For example, if the serial number of an anti-seepage sample is 1, then the anti-seepage parameter of that anti-seepage sample is 1; if the serial number of another anti-seepage sample is 2, then the anti-seepage parameter of that anti-seepage sample is 2.

[0067] Step 208: Based on the compressive strength parameters of multiple cement mixing pile samples, sort the compressive strength samples among the multiple cement mixing pile samples to obtain a compressive strength sample sequence.

[0068] The sum of compressive parameters is the sum of the unconfined compressive strength of the cement mixing pile sample on day n after manufacturing and on day 4n. In the compressive sample sequence, the index of each compressive sample is positively correlated with the sum of compressive parameters of the cement mixing pile sample it belongs to. For example, as shown in Table 5 above, the sum of compressive parameters for compressive sample A1B1C3 is the sum of the unconfined compressive strength (1.55 MPa) of the cement mixing pile sample on day 7 after manufacturing and on day 28 (2.63 MPa), which is 4.18 MPa. After calculating the sum of compressive parameters for all compressive samples, based on the positive correlation between the index of each compressive sample and the sum of compressive parameters of the cement mixing pile sample it belongs to, the nine compressive samples in Table 5 above are sorted, resulting in the following indices 1 to 9: The compressive strength parameters of the following samples are as follows: Sample 1 (A1B3C1) has a total compressive strength of 3.18 MPa; Sample 2 (A1B2C2) has a total compressive strength of 3.95 MPa; Sample 3 (A1B1C3) has a total compressive strength of 4.18 MPa; Sample 4 (A2B3C2) has a total compressive strength of 4.41 MPa; Sample 5 (A2B2C3) has a total compressive strength of 4.83 MPa; Sample 6 (A2B1C1) has a total compressive strength of 5.04 MPa; Sample 7 (A3B3C3) has a total compressive strength of 5.38 MPa; Sample 8 (A3B2C1) has a total compressive strength of 5.74 MPa; and Sample 9 (A3B1C2) has a total compressive strength of 5.80 MPa.

[0069] Step 209: Determine the serial number of each compressive strength sample as the compressive strength parameter of the cement mixing pile sample to which each compressive strength sample belongs.

[0070] In this step, the serial number of any compressive strength sample can be used to determine the compressive strength parameter of the cement mixing pile sample to which each compressive strength sample belongs. For example, if the serial number of a compressive strength sample is 1, then the compressive strength parameter of that compressive strength sample is 1; if the serial number of another compressive strength sample is 2, then the compressive strength parameter of that compressive strength sample is 2.

[0071] Step 210: Obtain the comprehensive parameters of each cement mixing pile sample from multiple cement mixing pile samples. The comprehensive parameters are the sum of the compressive strength parameters and the impermeability parameters of the cement mixing pile sample.

[0072] Cement mixing pile sample A2B3C2 has a compressive strength parameter of number 4 and a permeability parameter of number 1, therefore the comprehensive compressive strength parameter of sample A2B3C2 is 5; cement mixing pile sample A3B3C3 has a compressive strength parameter of number 7 and a permeability parameter of number 2, therefore the comprehensive compressive strength parameter of sample A3B3C3 is 9; cement mixing pile sample A1B3C1 has a compressive strength parameter of number 1 and a permeability parameter of number 3, therefore the comprehensive compressive strength parameter of sample A1B3C1 is 4; cement mixing pile sample A3B2C1 has a compressive strength parameter of number 8 and a permeability parameter of number 4, therefore the comprehensive compressive strength parameter of sample A3B2C1 is 12; cement mixing pile sample A2B2C3 has a compressive strength parameter of number 5 and a permeability parameter of number 2, therefore the comprehensive compressive strength parameter of sample A2B3C2 ...12; cement mixing pile sample A2B2C3 has a compressive strength parameter of number 5 and a permeability parameter of number 2, therefore the comprehensive compressive strength parameter of sample A2B3C2 is 9. The compressive strength parameter of sample A2B2C3 is 10, as it is number 5. For sample A1B1C3, the compressive strength parameter is number 3 and the impermeability parameter is number 6, therefore the comprehensive parameter is 9. For sample A1B2C2, the compressive strength parameter is number 2 and the impermeability parameter is number 7, therefore the comprehensive parameter is 9. For sample A2B1C1, the compressive strength parameter is number 6 and the impermeability parameter is number 8, therefore the comprehensive parameter is 14. For sample A3B1C2, the compressive strength parameter is number 9 and the impermeability parameter is number 9, therefore the comprehensive parameter is 18.

[0073] Step 211: Determine the sample parameter group corresponding to the cement mixing pile sample with the largest comprehensive parameters as the target parameter group.

[0074] The cement mixing pile sample with the highest comprehensive parameters is cement mixing pile sample A3B1C2. The sample parameter group corresponding to cement mixing pile sample A3B1C2 is 25% cement content, 10% phosphogypsum content, and 1% early strength agent content. This sample parameter group is determined as the target parameter group.

[0075] Step 212: Manufacture cement mixing piles based on the target parameter set.

[0076] Orthogonal experiments revealed that cement had the most significant impact on the strength of cement-soil mixing piles on days 7 and 28. In the early stages, the effect of accelerator was greater than that of phosphogypsum. On day 28, phosphogypsum showed greater hardness than accelerator. The permeability of cement-soil mixing piles exhibited different changes. On day 7, the effect was phosphogypsum > accelerator > cement, while on day 28, it was phosphogypsum > cement > accelerator. A small amount of gypsum contributed beneficially to the strength and permeability of cement-soil mixing piles, while excessive gypsum content reduced the strength and increased the permeability. Similarly, it was found that accelerator was beneficial to the strength and permeability of cement-soil mixing piles, with better effects in the early stages.

[0077] The cement mixing piles obtained based on the above target parameter set can achieve the highest compressive strength and the lowest permeability coefficient on the 28th day, and will not cause other damage due to excessive phosphogypsum, thus achieving the goal of rapid pile formation and meeting the requirements of engineering design.

[0078] In summary, the method for manufacturing cement-mixed piles in soft soil in coastal areas provided in this application involves conducting permeability and compressive strength tests on multiple cement-mixed pile samples to obtain permeability and compressive strength coefficient sets for each sample. Both sets include data from day n and day 4n. Based on these data, the permeability and compressive strength parameters for each sample are determined, and a comprehensive parameter for each sample is obtained. Cement-mixed piles can then be manufactured based on the parameter set corresponding to the sample with the highest comprehensive parameter. This method not only comprehensively considers the permeability and compressive strength parameters of the cement-mixed pile samples but also acquires these parameters at different times and considers the overall performance of cement-mixed pile samples manufactured from different parameter sets, thereby improving the performance of the manufactured cement-mixed piles.

[0079] In this application, the terms "first," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance. The term "multiple" refers to two or more unless otherwise expressly defined.

[0080] The above description is merely an optional embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for manufacturing cement-mixing piles in soft soil in coastal areas, characterized in that, The method for manufacturing cement-mixed piles for use in soft soil subgrades in coastal areas includes: Multiple sample parameter groups are determined, each sample parameter group including the cement content, phosphogypsum content and crystal nucleation early strength agent content in cement mixing piles, and at least one of the cement content, phosphogypsum content and crystal nucleation early strength agent content in any two sample parameter groups is different. Manufacture multiple cement mixing pile samples corresponding to the multiple sample parameter sets; The multiple cement mixing pile samples were subjected to permeability and compressive strength tests, and the permeability coefficient group and compressive strength coefficient group of each cement mixing pile sample were obtained. The permeability coefficient group includes the permeability coefficient of the cement mixing pile sample on the nth day after manufacturing and the permeability coefficient on the 4nth day after manufacturing. The compressive strength coefficient group includes the unconfined compressive strength of the cement mixing pile sample on the nth day after manufacturing and the unconfined compressive strength on the 4nth day after manufacturing, where n≥7. Based on the permeability coefficient group of the multiple cement mixing pile samples, the anti-seepage parameter of each cement mixing pile sample is determined, and the anti-seepage parameter is negatively correlated with the permeability coefficient in the permeability coefficient group; Based on the compressive strength coefficient group of the multiple cement mixing pile samples, the compressive strength parameter of each cement mixing pile sample is determined, and the compressive strength parameter is positively correlated with the unconfined compressive strength in the compressive strength coefficient group; Obtain the comprehensive parameters of each cement mixing pile sample from the plurality of cement mixing pile samples. The comprehensive parameters are the sum of the compressive strength parameters and the impermeability parameters of the cement mixing pile sample. The sample parameter group corresponding to the cement mixing pile sample with the largest comprehensive parameter is determined as the target parameter group; The cement mixing pile is manufactured based on the target parameter set.

2. The method according to claim 1, characterized in that, Each of the cement mixing pile samples includes at least one impermeable sample and at least one compressive strength sample; The process of performing impermeability tests and compressive strength tests on the multiple cement mixing pile samples includes: The impermeability sample was subjected to an impermeability test, and the permeability coefficient of the impermeable sample on the nth day after manufacturing and on the 4nth day were obtained based on the permeability coefficient calculation formula, wherein the permeability coefficient calculation formula includes: ; Where, k t Where A is the permeability coefficient, Q is the total seepage within time t, L is the spacing of the pressure measuring holes when performing a permeability test on the permeability sample, A is the cross-sectional area of ​​the permeability sample, H is the hydraulic head difference, and T is time. The compression test was performed on the compression-resistant sample.

3. The method according to claim 2, characterized in that, The determination of the impermeability parameters for each cement mixing pile sample based on the permeability coefficient set of the plurality of cement mixing pile samples includes: Based on the permeability parameters of the multiple cement mixing pile samples, the anti-permeability samples in the multiple cement mixing pile samples are sorted to obtain an anti-permeability sample sequence. The permeability parameters are the sum of the permeability coefficients of the anti-permeability samples in the cement mixing pile samples on the nth day after manufacturing and the permeability coefficients on the 4nth day. In the anti-permeability sample sequence, the number of each anti-permeability sample is negatively correlated with the permeability parameters of the cement mixing pile sample in which it belongs. The serial number of each anti-permeability sample is determined as the anti-permeability parameter of the cement mixing pile sample to which each anti-permeability sample belongs.

4. The method according to claim 2, characterized in that, The determination of the compressive strength parameters for each cement mixing pile sample based on the compressive strength coefficient group of the multiple cement mixing pile samples includes: Based on the compressive strength parameters of the multiple cement mixing pile samples, the compressive strength samples in the multiple cement mixing pile samples are sorted to obtain a compressive strength sample sequence. The compressive strength parameters are the sum of the unconfined compressive strength of the compressive strength samples in the cement mixing pile samples on the nth day after manufacturing and the unconfined compressive strength on the 4nth day. In the compressive strength sample sequence, the number of each compressive strength sample is positively correlated with the compressive strength parameters of the cement mixing pile sample in which it belongs. The serial number of each compressive strength sample is determined as the compressive strength parameter of the cement mixing pile sample to which each compressive strength sample belongs.

5. The method according to claim 2, characterized in that, The determination of multiple sample parameter groups includes: The three cement admixture amounts are determined to be 15%, 20%, and 25%, respectively, and the cement admixture amount is the mass ratio of cement to clay in the cement mixing pile. The three phosphogypsum dosages are determined to be 10%, 20%, and 30%, respectively, and the phosphogypsum dosage is the mass ratio of phosphogypsum to clay in the cement mixing pile. The dosages of the three early-strength nucleating agents were determined to be 0.5%, 1%, and 1.5%, respectively, and the dosage of the early-strength nucleating agent was the mass ratio of the early-strength nucleating agent to the clay in the cement mixing pile. Nine sample parameter groups were obtained based on the three cement dosages, the three phosphogypsum dosages, the three nucleation early strength agent dosages, and the orthogonal experimental method.

6. The method according to claim 5, characterized in that, The manufacturing of multiple cement mixing pile samples corresponding to the multiple sample parameter sets includes: Obtain the clay from the soft soil subgrade; The clay is dried and impurities are removed by sieving to obtain sieved clay. Water is added to the screened clay to obtain the target clay, the moisture content of which is the same as that of the clay in the soft soil subgrade. Based on the cement content, phosphogypsum content, and crystal nucleation early strength agent content in the first sample parameter group among the multiple sample parameter groups, cement, phosphogypsum, and crystal nucleation early strength agent are obtained. The nucleation early strength agent is dissolved in water, and the cement and phosphogypsum are mixed at a water-to-solid ratio of 0.5 to obtain cement slurry. The cement slurry is poured into the mold of the cement mixing pile sample; The mold containing the cement slurry was placed in a curing room and left to stand for 24 hours. The mold is demolded to obtain the cement mixing pile sample.

7. The method according to claim 6, characterized in that, The cement contains the following components in the following mass proportions: 27.19% silicon dioxide, 11.32% aluminum oxide, 3.76% ferric oxide, 51.78% calcium oxide, 1.98% magnesium oxide, and 3.97% sulfur trioxide.

8. The method according to claim 6, characterized in that, The phosphogypsum contains the following components in the following mass proportions: 9.01% silicon dioxide, 2.01% aluminum oxide, 0.49% ferric oxide, 35.41% calcium oxide, 0.21% magnesium oxide, and 52.87% sulfur trioxide.

9. The method according to claim 6, characterized in that, The process of filling the mold with the cement slurry into the cement mixing pile sample includes: The cement slurry is injected into the anti-permeability mold and the pressure-resistant mold. Both the anti-permeability mold and the pressure-resistant mold are columnar. The diameter of the anti-permeability mold is 39.1 mm and the height is 80 mm. The diameter of the pressure-resistant mold is 50 mm and the height is 100 mm. The anti-permeability mold is used to manufacture the anti-permeability sample, and the pressure-resistant mold is used to manufacture the pressure-resistant sample.

10. The method according to any one of claims 1 to 9, characterized in that, Before determining the compressive parameters of each cement mixing pile sample based on the compressive coefficient group of the plurality of cement mixing pile samples, the method further includes: Determine whether there exists a group of compressive coefficients among the plurality of cement mixing pile samples whose unconfined compressive strength on the 4nth day after manufacturing is less than the preset unconfined compressive strength. When present, remove the group of compressive strength coefficients whose unconfined compressive strength on the 4nth day after manufacturing is less than the preset unconfined compressive strength.

Citation Information

Patent Citations

  • Supersulfide phosphogypsum phosphorus slag cement concrete product and preparation method thereof

    CN111848093A

  • Comprehensive evaluation method of quality control factors of cement mixing piles

    CN112411640A

  • Soft soil zone cement mixing pile slurry admixture

    CN116375382A

  • Variable installation type wave prevention device

    KR1020210148752A